2022
DOI: 10.1016/j.cgh.2020.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Cold Snare Polypectomy Without Submucosal Injection for Large Sessile Serrated Lesions: A Prospective Study

Abstract: BACKGROUND & AIMS:Cold snare polypectomy (CSP) has become the standard resection method for small colorectal polyps (<10 mm). Sessile serrated lesions (SSL) have low prevalence of advanced histology irrespective of size, and thus could be amenable to CSP. In this study, we evaluated the safety and efficacy of CSP for SSLs ‡10 mm. METHODS:Between November 2018 and January 2020, we prospectively enrolled 300 consecutive patients who underwent CSP for 474 SSLs ‡10 mm. To delineate SSL borders, indigo carmine chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“… 29 , 45 In this context, several authors assessed CSP specifically for serrated lesions. 31 , 32 , 33 A systematic review analyzed 1137 SSP ≥ 10 mm compared the outcomes of cold and hot EMR and found a lower residual polyp rate in the cold EMR group in univariate analysis (0.9% vs. 5.0%), although there were no differences in multivariate regression analysis. 44 Since this systematic review, recent studies confirmed low recurrence rates after CSP of SSL (0%–8%; Table 2 ).…”
Section: Current Management For Colorectal Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 , 45 In this context, several authors assessed CSP specifically for serrated lesions. 31 , 32 , 33 A systematic review analyzed 1137 SSP ≥ 10 mm compared the outcomes of cold and hot EMR and found a lower residual polyp rate in the cold EMR group in univariate analysis (0.9% vs. 5.0%), although there were no differences in multivariate regression analysis. 44 Since this systematic review, recent studies confirmed low recurrence rates after CSP of SSL (0%–8%; Table 2 ).…”
Section: Current Management For Colorectal Lesionsmentioning
confidence: 99%
“…In this study 474 SSL were resected without submucosal injection and only one recurrent adenoma was found after 7 months follow up. 32 …”
Section: Current Management For Colorectal Lesionsmentioning
confidence: 99%
“…W E EXTRACTED 15 studies that reported on CSP for large (≥1 cm) colorectal polyps. These included four prospective single arm studies, [39][40][41][42] 10 retrospective studies, [43][44][45][46][47][48][49][50][51][52] and one prospective RCT 20 (Table 3).…”
Section: Cold Procedures For Large (≥1 Cm) Colorectal Polypsmentioning
confidence: 99%
“…Three prospective studies only included large (>10 mm) sessile serrated lesions (SSL), [39][40][41] and one prospective study included polyps measuring 10-15 mm. 42 Two of the studies assessed the completeness of resection by using biopsies from the mucosal defect after CSP, which illustrated excellent endoscopic CRR (98%).…”
Section: Cold Procedures For Large (≥1 Cm) Colorectal Polypsmentioning
confidence: 99%
See 1 more Smart Citation